Gambaran Pengetahuan Ibu Tentang Imunisasi Hb-0 di TPMB “L” Kabupaten Ciamis - Firdaus, Firna Nakhwa; Fatimah, Siti; Rohmah, Siti; Lestari, Ririn (Universitas Galuh, 2023)
Data from the Ministry of Health of the Republic of Indonesia shows that as many as 7.1% or 18 million Indonesians are infected with Hepatitis B-0. Of these, 50% are at risk of becoming chronic and 900,000 can become liver cancer. Even Hepatitis B-0 is the top 4 cause of death in Indonesia, with an estimated annual death of 51,100 deaths. HB-0 immunization coverage at TPMB